Formulasi dan Karakterisasi Mi Kering Substitusi Tepung Kacang Merah Tinggi Serat - Dina Widiawati; Sarah Giovani; Sefira Putri Liana (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2022)
Making dry noodles from red bean flour substitution is one way to reduce the consumption of wheat flour in Indonesia and this dry noodle can be a functional food product. This study aims to determine the best substitution formula of red bean flour favored by panelists and to determine the results of physicochemical testing of the resulting dry noodles. The ratio of flour used between wheat flour and red bean flour is 90%:10%, 80%:20%, and 70%:30%. This study used a Completely Randomized Design (CRD) with Duncan's further test. The results of the analysis of variance based on physical and chemical tests on dry noodles were not significantly different for each treatment at the 5% level. Meanwhile, the organoleptic test showed a significant difference in color (before and after the presence), but no significantly different in texture, aroma, and taste. The 10% red bean flour substitution treatment resulted in dry noodles which were favored by the panelists. This noodle has 86,07%±1,90 water absorption, 4,95%±0,12 cooking loss, 9,16%±0,45 water content, 2,15%±0,89 ash content, 7,62%±0,87 protein, 1,01%±1,14 fat, 80,04%±1,01 carbohydrates, and 3,88%±1,05 dietary fiber. Panelists on color before launching (somewhat like); color after (rather like); texture (rather like); aroma (slightly like), and taste (slightly like). Dry noodles with the addition of 10% red bean flour can be said to be a functional food source of fiber because the dietary fiber is 3.88%. This also shows that the fiber content of dry noodles substituted with red bean flour can be a source of functional food.Keywords – Physicochemistry, Characterization, Dried Noodles, Dietary Fiber, Red Bean Flour